2019
DOI: 10.3390/electronics8121499
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Activities of Daily Living and Environments Using Acoustic Sensors Embedded on Mobile Devices

Abstract: The identification of Activities of Daily Living (ADL) is intrinsic with the user’s environment recognition. This detection can be executed through standard sensors present in every-day mobile devices. On the one hand, the main proposal is to recognize users’ environment and standing activities. On the other hand, these features are included in a framework for the ADL and environment identification. Therefore, this paper is divided into two parts—firstly, acoustic sensors are used for the collection of data to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 55 publications
(73 reference statements)
0
27
0
Order By: Relevance
“…According to the previously proposed structure of a framework for the recognition of ADL and environments [2,[17][18][19][20][21][22][23][24][25], the main focus of this study was related to the data classification module, taking into account the implementations of the other modules performed in previous studies. Previously, the DNN method was implemented, and it reported reliable results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the previously proposed structure of a framework for the recognition of ADL and environments [2,[17][18][19][20][21][22][23][24][25], the main focus of this study was related to the data classification module, taking into account the implementations of the other modules performed in previous studies. Previously, the DNN method was implemented, and it reported reliable results.…”
Section: Discussionmentioning
confidence: 99%
“…This study consisted of the use of the same structure and data acquired by the research presented in [18,21,22,24,25] to implement a comparative study between three types of studies. The tests were conducted with the dataset available in [24], which included data related to the eight ADL and nine environments.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has shown that personalized approaches and systematic feature engineering and selection can help in improving the activity recognition accuracy [22][23][24]. In addition to using inertial sensors (i.e., accelerometers and gyroscopes) embedded in mobile devices, acoustic sensors can augment and improve the activity and environment recognition [25,26]. However, these methods have several limitations that should be considered during the development of these systems, such as availability of the sensors, weather conditions, battery lifetime, limited power processing, and memory capabilities, among others [27,28].…”
Section: Introductionmentioning
confidence: 99%